A simplified method for evaluating singular stress field of V-shaped and U-shaped notches with different opening angle. (15th August 2020) - Shen, Wei; Qiu, Yu; Hu, Yaoyu; Liu, Enqian; Pan, Jin
Abstract: The existing stress field evaluation formulas for V-shaped and U-shaped notches are complicated and limited to certain specific opening angles. Based on linear elastic fracture mechanics and singular strength theory, the traditional calculation formula of notch stress distribution is simplified by introducing singular intensity factors, and the notch stress formula suitable for different opening angles is further summarized and fitted by comparing the stress distribution laws from 102° to 150° opening angles. After verification, the relative error of stress between the simple formula and finite element results is about 5%. On this basis, the formula of notch stress intensity factor (N-SIF) under different opening angles is further derived. Finally, the notch stress and N-SIF of cruciform welded specimens under different welding angles are separately calculated for fatigue strength evaluation. The evaluation process shows that the simplified formula can be used to quickly and accurately evaluate the notch stress field and fatigue strength of welded structures. Highlights: The traditional calculation formula of notch stress distribution was simplified by introducing singular intensity factors. The notch stress formula suitable for different opening angles was further summarized and fitted. The relationship between notch stress and notch stress intensity factor was established based on singular intensity factors.